(untitled) (Fiep Bulletin - online, 2013)
Pressure Ulcers (PUs) are defined by NPUAP as localized areas of necrotic tissue that tend to develop when a tissue is compressed between a bone prominence and an external surface for a long time. The PUs is configured as are a serious problem for both the patient as for the family and institution and, therefore, can cause pain, discomfort and suffering, in addition to increased morbidity and mortality, raising the costs of treatment. This study aimed to identify the intrinsic and extrinsic risk factors intrinsic and extrinsic in the occurrence of PUs in hospitalized patients. It is a descriptive study, with a longitudinal design and quantitative approach, with hospitalized patients in two hospitals, one public and one private, both located in Natal/RN. The population was made up of 52 patients bedridden. The research was assessed by the Commission on Ethics in Research/UFRN. Of the total of 52 bedridden patients, 51.9% developed PUs; of those, 77.8% were elderly, 59.3% male, 74.1% had amended COONEY JUNIOR., L.M. Pressure sores and urinary incontinence. J Am Geriatr superficial sensitivity, 96.3% had change in the texture of the skin, 70,4% edema, 81.5% showed changes in skin humidity, 65.2% had changes in body temperature and 96.3% had total impaired physical mobility, 81.5% had the pressure force in the body, 92.6 % had force of friction and shear. Among the 5 with total restriction of movement, 100% developed PUs, 100% were inadequately mobilized and 92.6% had inadequate bed linen conditions. The multicausality identified on the emergence of PUs references us to the importance of searching for information about the influence of the multiplicity of factors and conditions that increase the risk of PUs, with a view of contributing to the prevention and reduction of its complications, resulting in improved life quality.